PENGARUH PERMAINAN TRADISIONAL BEBENTENGAN TERHADAP MATERI LARI SPRINT PADA PELAJARAN PJOK KELAS V SD NEGERI 060871 MEDAN - Nabilah Assyifa Lubis Habib Khairuman Lubis; Winara; Waliyul Maulana Siregar; Putra Afriadi; Masta Marselina Sembiring (STKIP Subang, 2025)
This study aims to determine the effect of traditional games bebentengan in sprint running material in physical education lessons class V SD Negeri 060871 Medan. This type of research is quantitative research. The research method used is Experiment with One Group Pretest and Posttest Design design. The population used was class V SD Negeri 060871 Medan which amounted to 76 students. The sample used was purposive sampling technique, namely V-B 25 students. Data collection techniques used are test techniques, test scores. Based on the results of the study it was found that there was an effect of traditional games bebentengan. This is tested from the value of the average difference in sprint running time in the pre-test 3,76 and post-test 3,44. Based on the data obtained from the hypothesis test results for the data, namely 3,22 > 1.70, Ho is rejected and Ha is accepted. It can be concluded that “There is an Effect of Bebentengan Traditional Games on Sprint Running Material in Physical Education Class V State Elementary School 060871 Medan”. The results of the research on the traditional game method bebentengan obtained an increase in students' sprint running time so that it gave an influence on the ability to run sprints in students' running speed.